Analysis Environmental Sanitation Distribution Patterns Stunting Incidence in Silahisabungan Subdistrict - Deli Syaputri; Th Teddy Bambang S; Samuel Maganda H Manalu; Desy Ari Apsari; Riyanto Suprawihadi (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Stunting is a public health problem caused by chronic malnutrition and is often exacerbated by poor environmental sanitation. Environmental sanitation factors that cause it are clean water management, waste management, feces management and sewerage management. Improving sanitation infrastructure and promoting healthy living behaviors are essential to reduce stunting and support sustainable health outcomes. In Silahisabungan Subdistrict, Dairi Regency, this study is to examine the distribution pattern of environmental cleanliness and its relationship to the prevalence of stunting. This type of research is observational with a case control design and ecological approach, to obtain an overview of the distribution patterns of stunting and environmental sanitation using geographic information system applications. The case sampling technique used total sampling. Where all stunted toddlers were taken as cases as many as 58 toddlers and controls as many as 58 toddlers. Purposive sampling was used to conduct the research sampling. This study's data was analysed using univariate, bivariate, and multivariate methods, including logistic regression, chi-square statistical tests, and mapping of stunting data using Google Earth and Quantum GIS. The results showed that there was a significant relationship between water management (p-value=0.000), waste management (p-value=0.032), waste management (p-value=0.000) and there was no significant relationship between feces management (p-value=0.193) with the incidence of stunting. Improving environmental sanitation is a key factor in reducing the prevalence of stunting. Interventions that focus on increasing access to clean water, building sanitation facilities, and educating the community about clean and healthy living behaviors need to be prioritized. Keywords: Environmental Sanitation, Distribution Pattern, Stunting